A carreira de delegado de polícia civil do estado do Tocantins: a influência da hierarquia e das propriedades sociais na trajetória profissional - Lyra Filho, Afonso José Azevedo de (Universidade Federal do Tocantins, 2022)
The present research had as general objective the analysis of the trajectory of the members of the legal career of Civil Police Delegado of the State of Tocantins, applying the theory of social fields of Pierre Bourdieu. Through the analysis of the trajectory of the career members, it was possible to identify the social capitals that influence the power and strength relationships within the field, which determine the positioning of the professionals within the general career struc- ture. The analysis of the trajectory began with the collection of data that indicate the capital required for entering the career, which presupposes approval in the public tender for the position of Police Delegado, which for being of a legal nature, requires a degree in law. The main data related to the career were raised, addressing historical, legal, doctrinal and social aspects of the career, which allowed the construction of the genesis of the present research. Theoretical basis is based on Pierre Bourdieu's theory of social fields, having been approached the main concepts of the theory, relating it to the object of study, in this case the trajectory of the police delegados of the State of Tocantins. The research was carried out in the city of Palmas, through interviews, collection of official data published in the Official Gazette of the State of Tocantins, as well as the dissemination of a semi-structured questionnaire (Annex) to all members of the career of Civil Police delegados of the State of Tocantins. As an exclusion criterion, those retired or on sick leave for more than 12 months will be excluded from the survey. Through the data collected in the research, 57 prosopographs were performed, which were used in the analysis of multiple correspondences (ACM) to position career members within the social field, revealing the rela- tive weight of social capitals that influence power relations. The study intends to contribute to the study of professions, in the case of the career of Civil Police Delegados of the State of Tocantins, this career is responsible for providing part of the public service related to public security at the state level.